2022
DOI: 10.2174/2666082218666220325105504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Symptoms and Features During the Infection Period on the Level of Anxiety and Depression of Adults after Recovery from COVID-19

Abstract: Background: Considering the previous evidence regarding SARS/MERS outbreaks, ıt is expected that emergent psychiatric conditions such as mood disorders, anxiety, and depression disorders may occur in survivors of COVID-19. Objectives: In this study, the effects of clinical/neurological symptoms and sociodemographic characteristics of COVID-19 patients during the infection period on the level of anxiety/depression after recovery were investigated. Methods: Firstly, the socio-demographic characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…COVID-19 has attracted attention for its higher infectivity and mortality than influenza [ 1 , 3 , 41 ]. The majority of infected patients had mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has attracted attention for its higher infectivity and mortality than influenza [ 1 , 3 , 41 ]. The majority of infected patients had mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has a higher mortality and infectivity than influenza [ 3 , 13 ]. The disease still causes death and continues to spread [ 1 , 6 , 15 ]. The use of vaccines did not stop the spread of the disease, and important mutations were detected in the structure of the virus during the epidemic [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML) and AI studies based on RBVs features are a more economical and rapid alternative method for the early detection, diagnosis and prognosis of COVID-19 [ 7 , 11 , 12 ]. Previous studies have indicated that this disease can accompany multi-organ dysfunction and cause a variety of symptoms [ 3 , 13 , 14 , 15 ]. COVID-19 can cause severe pneumonia and severe ARDS due to inflammatory cytokine storms [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While new studies continue to diagnose SARS-CoV-2, many of these applications require specialized teams and specialized equipment, increasing the cost [9] , [10] , [11] , [12] . It is extremely important that new technological applications for the diagnosis and determination of the prognosis of the disease are easily accessible to every society and can be used quickly and effectively without creating an existence problem [ 10 , 11 , 13 ].…”
Section: Methods Detailsmentioning
confidence: 99%